A pilot test of the new Swiss regulatory procedure for categorizing clinical trials by risk: A randomized controlled trial. (December 2015) - Cevallos, Myriam; Züllig, Stephanie; Christen, Andri; Meier, Brigitte E; Goetz, Martin; Coslovsky, Michael; Trelle, Sven
Background/Aims: Several countries are working to adapt clinical trial regulations to align the approval process to the level of risk for trial participants. The optimal framework to categorize clinical trials according to risk remains unclear, however. Switzerland is the first European country to adopt a risk-based categorization procedure in January 2014. We assessed how accurately and consistently clinical trials are categorized using two different approaches: an approach using criteria set forth in the new law (concept) or an intuitive approach (ad hoc). Methods: This was a randomized controlled trial with a method-comparison study nested in each arm. We used clinical trial protocols from eight Swiss ethics committees approved between 2010 and 2011. Protocols were randomly assigned to be categorized in one of three risk categories using the concept or the ad hoc approach. Each protocol was independently categorized by the trial's sponsor, a group of experts and the approving ethics committee. The primary outcome was the difference in categorization agreement between the expert group and sponsors across arms. Linear weighted kappa was used to quantify agreements, with the difference between kappas being the primary effect measure. Results: We included 142 of 231 protocols in the final analysis (concept = 78; ad hoc = 64). Raw agreement between the expert group and sponsors was 0.74 in the concept and 0.78 in the ad hoc arm. Chance-corrected agreement was higher in the ad hoc (kappa: 0.34 (95% confidence interval = 0.10–0.58)) than in the concept arm (0.27 (0.06–0.50)), but the difference was not significant (p = 0.67). Limitations: The main limitation was the large number of protocols excluded from the analysis mostly because they did not fit with the clinical trial definition of the new law. Conclusion: A structured risk categorization approach was not better than an ad hoc approach. Laws introducing risk-based approaches should provide guidelines, examples and templates to ensure correct application.